Integrative metabolome and transcriptome analyses reveal the molecular mechanism underlying variation in floral scent during flower development of Chrysanthemum indicum var. aromaticum - Zhu, Lu; Liao, Jiahao; Liu, Yifei; Zhou, Chunmiao; Wang, Xu; Hu, Zhigang; Huang, Bisheng; Zhang, Jingjing (Frontiers in Plant Science, 2022)
Chrysanthemum indicum var. aromaticum (CIA) is an endemic plant that occurs only in the high mountain areas of the Shennongjia Forest District in China. An intense fragrance is present throughout the whole plant, particularly in the flowers, making it a novel resource for agricultural, medicinal, and industrial applications. However, the volatile metabolite profile of CIA and the molecular mechanisms underlying its floral scent remain poorly understood. Here, integrative metabolome and transcriptome analyses were performed to investigate floral scent–related volatile compounds and genes in CIA flowers at three different developmental stages. A total of 370 metabolites, mainly esters and terpenoids, were identified, 89 of which were present at different levels in samples from different stages. Transcriptome analysis yielded 104,165 expressed genes and 8,945 differentially expressed genes (DEGs). KEGG enrichment analyses of the DEGs identified 93, 101, and 45 candidate genes associated with the phenylpropanoid, ester, and terpene biosynthesis pathways, respectively. Among these genes, PAL, CYP98A/C3H, 4CL, CHS, GGPS, and TPS14 may play important roles in regulating the formation of the CIA floral scent. These findings provide insights into the molecular basis of plant floral scent metabolite biosynthesis and serve as important data resources for molecular breeding and utilization of CIA plants in the future.